2017
DOI: 10.1007/s00383-017-4069-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin D, a steroidal saponin in Paris polyphylla, induces apoptosis and necroptosis cell death of neuroblastoma cells

Abstract: Together, this indicates that the underlying mechanism of polyphyllin D-induced cell death in NB-69 cells is apoptosis, whereas the cell death of IMR-32 and LA-N-2 cells occurs by necroptosis. We continue research on this topic and look forward the discovery of a new therapeutic agent for neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Polyphyllin D induced apoptosis and necrosis in cells in a caspase-dependent manner as we reported previously [11]. Arctigenin also induced apoptosis in lung cancer, breast cancer, gallbladder cancer, hepatocellular carcinoma, and colorectal cancer cells [5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Polyphyllin D induced apoptosis and necrosis in cells in a caspase-dependent manner as we reported previously [11]. Arctigenin also induced apoptosis in lung cancer, breast cancer, gallbladder cancer, hepatocellular carcinoma, and colorectal cancer cells [5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 76%
“…Previously, we treated cells from a neuroblastoma cell line with polyphyllin D and observed its antitumor effects. The results of our experiment indicated that necroptosis occurred in a cell line with the MYCN gene, while apoptosis occurred in a cell line lacking the MYCN gene [11]. Although the pathways mediating the antitumor effect of arctigenin are different in various tumors, apoptosis induction occurs in all tumors [5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 213 ). Other agents inducing necroptosis in RIPK3-expressing NB cells are polyphyllin D 214 and d -gal 215 . On the other hand, many NBs have a decreased expression of caspase-8 and low level of proteins involved in necroptosis, especially in the advanced stages, making them also resistant to necroptosis induction 216 .…”
Section: Targeting Nb Via Stimulation Of Various Modes Of Cell Deathmentioning
confidence: 99%
“…The herb Paris polyphylla is a traditional Chinese drug that has heat-clearing and detoxicating effects. Polyphyllin D (PD) is the major component of Paris polyphylla, and it has been used to treat such ailments as convulsions, mastitis, and tumors of the respiratory system, as well as leukemia (3,4,5). Studies have shown that PD functions as an anti-tumor agent through the inhibition of cell proliferation and by inducing apoptosis in several tumor cell types (5,6,7).…”
mentioning
confidence: 99%